The Role of Hematological Indices in the Diagnosis of Iron deficiency Anemia in patient at Zliten Medical Center - Mufeedah Saud; Muhammad Alhaleeb (Libyan Journal of Medical and Applied Sciences, 2025)
Anemia represents a significant global health concern, affecting populations across both developing and developed nations. A central debate in the medical field concerns the appropriate hemoglobin threshold that should be used to define anemia, particularly in the elderly population. Among nutritional deficiencies, iron deficiency remains the most prevalent worldwide, impacting more than two billion individuals. Its most serious manifestation, iron deficiency anemia (IDA), is recognized as a major public health problem, disproportionately affecting individuals in low- and middle-income countries. The present study sought to. evaluate the utility of red blood cell (RBC) indices.as a screening tool.for the. Early detection. of iron deficiency. A descriptive cross-sectional study was conducted at Zliten Medical Center between October 2022 and April 2023, involving 150 patients diagnosed with IDA. Complete blood count (CBC) parameters were analyzed, including RBC count (×10³/μl), hemoglobin concentration (Hb, g/dl), mean corpuscular volume (MCV, fL), and mean corpuscular hemoglobin (MCH, pg). The study cohort consisted of 150 anemic patients, comprising 90 females (60%) and 60 males (40%), with a mean age of 40 years. Results indicated that the mean Hb level was 8 g/dl in females and 9 g/dl in males. The average MCV was 70 fL in females and 75 fL in males, while the mean MCH values were 20 pg and 24 pg, respectively. Additionally, serum ferritin levels were consistently below 100 ng/ml. The findings suggest that iron deficiency can be reliably predicted at an early stage through the assessment of Hb and RBC indices. This approach represents a cost-effective alternative to more advanced diagnostic methods and could be particularly valuable in resource-limited settings.